Skin fragility syndrome in a cat with multicentric follicular lymphoma. Issue 10 (October 2013) - Crosaz, Odile; Vilaplana-Grosso, Federico; Alleaume, Charline; Cordonnier, Nathalie; Bedu-Leperlier, Anne-Sophie; Marignac, Geneviève; Hubert, Blaise; Rosenberg, Dan
An 11-year-old, spayed female domestic shorthair cat was presented for a right flank wound. On clinical examination, a single non-painful skin tear lesion with irregular edges was detected. During the examination, star-shaped cigarette paper-like skin lesions appeared spontaneously. An abdominal mass was also palpated. Feline skin fragility syndrome (FSFS) was suspected and a multicentric lymphoma was diagnosed by fine needle aspiration. The cat's condition declined and it died spontaneously. Post-mortem examination confirmed the diagnosis of lymphoma. Neoplastic lymphocytes were not observed in the skin. Histological analysis of the skin was consistent with the morphological aspects of FSFS. A possible direct link between the two conditions remains a matter of speculation, but this case report provides the first description of FSFS associated with multicentric follicular lymphoma. Thus, multicentric follicular lymphoma should be considered as a differential diagnosis in cats presenting with FSFS.